Articular Disc of a Human Temporomandibular Joint: Evaluation through Light Microscopy, Immunofluorescence and Scanning Electron Microscopy - Michele Runci Anastasi; Piero Cascone; Giuseppe Pio Anastasi; Giuseppe Santoro; Fabiana Nicita; Giacomo Picciolo; Angelo Favaloro; Giuseppina Rizzo; Giuseppina Cutroneo (Journal of Functional Morphology and Kinesiology, 2021)
The extracellular matrix of the articular disc in a temporomandibular joint (TMJ) is composed mainly of collagen I and elastin. The collagen is important for resisting tensile forces, while the elastin is responsible to maintain the shape after deformation. We studied the orientation of collagen and elastin in a normal human temporomandibular joint disc by light microscopy, immunofluorescence and scanning electron microscopy. Our results demonstrated that collagen and elastin run parallel to each other in the intermediate zone with an anteroposterior orientation. From here, the orientation of two fibers groups changes into a disordered arrangement in the transition zone. Numerous elastic fibers cross with the collagen fibers, defining an interwoven knitted arrangement. The evaluation of the disc–condyle relationship shows that the medial margin of the articular disc is inserted directly at the superficial layer of the mandibular condylar cartilage. Therefore, the tensile properties of the TMJ disc are expressed in the directions corresponding to the orientation of the collagen fibers, and the complex orientation of elastin with the collagen determines the maintaining of the shape after the stresses by the joint movements. Moreover, the direct anatomical relationship between the articular disc and the mandibular condyle makes a decisive contribution to the understanding of TMJ movements.